Antibiotic Stewardship and Resistance: Knowledge, Attitude, and Perception of Undergraduate Medical Students: Antibiotic Stewardship and Resistance: Knowledge, Attitude, and Perception of Undergraduate Medical Students - Deo, Dr. Satish Kumar (International Journal of Pharmaceutical & Biological Archive, 2020)
Introduction: This study aim to evaluate the knowledge, attitude, and perception of undergraduate medical students about antibiotic stewardship. A questionnaire-based survey was conducted among the medical students of Maharajgunj Medical Campus, Nepal from both basic (first two years) and clinical sciences (third year onwards). Materials and Methods: Responses were scored to assess the knowledge level of the students, their attitude and perception towards antibiotic stewardship and resistance. Results: In this study, 231 out of 450 undergraduate medical students (response rate=51.33%) took part. The mean knowledge, attitude and perception scores of the respondents were 2.41±1.103, 5.69±0.917, and 13.10±1.328 respectively. Though their overall attitude [223 (96.5%)] and perception [230 (99.6%)] towards antibiotic stewardship and resistance were good, their knowledge level seemed unsatisfactory [105 (45.5%)]. Statistically significant difference in the scores between basic science and clinical science students (P<0.001) was seen. Discussion: More than half the medical students’ knowledge about antimicrobial stewardship and resistance was inadequate. A perceivable difference between scores of basic and clinical science students was observed, suggesting that the knowledge, attitude, and perception of basic science students get better as they enter clinical phase. Conclusion: Suitable interventions to address the lag in curriculum should be planned right from basic science level to further strengthen their knowledge regarding antibiotic stewardship and resistance.